The voluntary carbon market: market failures and policy implications - Battocletti, V; Enriques, L; Romano, A (European Corporate Governance Institute, 2023)
Companies that have announced climate targets (for instance: becoming “net zero” by 2050) represent a market capitalization of over $20 trillion. Almost all of them will rely on carbon offsets to reach their goal. In this Article we investigate the functioning of the market on which these offsets are created and exchanged, namely the voluntary carbon market, and look into the question of whether, and if so, how it should be subject to regulation. We start out by shedding light on the mechanics of this market and then explain why a well-functioning voluntary carbon market is necessary to fight global warming and can also help developing countries build less carbon-intensive economies. However, we also spotlight the conflicts of interest and imperfect information problems that plague the voluntary carbon market and prevent it from achieving its full potential. Further, we explain why the proposals advanced by some Members of the Congress to regulate this market are misguided. Finally, we offer a simple policy recipe that can contribute to improving the functioning of the voluntary carbon market, thus increasing the likelihood that firms will rely on high-quality offsets to reach their climate goals.